Antimicrobial resistance in fecal Escherichia coli from different pig production system - Jamlong Mitchaothai; Kanokrat Srikijkasemwat (My University, 2021)
The objective of the current study was to investigate the influences of conventional (CO) and deep litter (DE) systems on antimicrobial resistance in fecal Escherichia coli (E. coli).A cross-sectional study was carried out to detect antimicrobial resistance to E. coli in swine fecal samples in CO and DE systems located in western and northeastern Thailand. Individual rectal swab samples were taken only from healthy pigs. A total of 215 individual and healthy pigs were randomly selected for isolation and antimicrobial susceptibility test of E. coli by the disc diffusion method. The test panel included amoxicillin (AMX), colistin, doxycycline (DOX), enrofloxacin, gentamicin (GEN), kanamycin, neomycin (NEO), and trimethoprim-sulfamethoxazole (SXT).There were significant (p<0.05) lower resistance levels for GEN, NEO, and SXT in the DE farms compared to those in the CO farms. There was a lower number of antimicrobial resistance agents (p<0.001) in the DE farms compared to those in the CO farms. This result was consistent with those in western (p<0.01) and northeastern (p<0.01) Thailand. Overall, antibiograms of AMX-SXT and AMX-DOX-SXT were found in the CO (19.09% and 20.91%, respectively) and the DE (16.19% and 24.76%, respectively) farms. No antimicrobial resistance (5.71%) was found and AMX (13.33%) resistant pigs in the DE farms, whereas the pattern of AMX-GEN-SXT (6.36%) and AMX-DOX-GEN-SXT (11.82%) resistant pigs was found in the CO farms.The DE system for pig farming was superior to conventional pig farming by lowering the resistance level of fecal E. coli to GEN, NEO, and SXT, with decreasing the number of antimicrobial resistance agents and inducing a small proportion of pigs to be free from antimicrobial resistance.
Keywords: Colistin; Trimethoprim; Pharmaceutical and Antibiotic Environmental Impacts